Involvement of Protein Kinase CgSat4 in Potassium Uptake, Cation Tolerance, and Full Virulence in Colletotrichum gloeosporioides - Pan, Yu-Ting; Li, Lianwei; Yang, Ji-Yun; Li, Bing; Zhang, Yun-Zhao; Wang, Ping; Huang, Lin (Frontiers in Plant Science, 2022)
The ascomycete Colletotrichum gloeosporioides is a causal agent of anthracnose on crops and trees and causes enormous economic losses in the world. Protein kinases have been implicated in the regulation of growth and development, and responses to extracellular stimuli. However, the mechanism of the protein kinases regulating phytopathogenic fungal-specific processes is largely unclear. In the study, a serine/threonine CgSat4 was identified in C. gloeosporioides. The CgSat4 was localized in the cytoplasm. Targeted gene deletion showed that CgSat4 was essential for vegetative growth, sporulation, and full virulence. CgSat4 is involved in K+ uptake by regulating the localization and expression of the potassium transporter CgTrk1. CgSat4 is required for the cation stress resistance by altering the phosphorylation of CgHog1. Our study provides insights into potassium acquisition and the pathogenesis of C. gloeosporioides.